The selected aspects of emotional labour and emotion regulation in medical jobs - Maciej Załuski; Marta Makara-Studzińska (Kazimierz Wielki University, 2017)
Background: the term of emotional labour describes the processes which occur at the medical staff while carrying out emotional expectations of patients. There are links between emotional labour, work strain and the exhaustion of physical and emotional strenght. Goal of dissertation: to discuss certain problems connected with the phenomenon of the emotional labour and the emotion regulation processes which occur to the medical staff during the contact with patients. Summary and conclusion: there are a lot of research which confirm the negative health effects of some kinds of emotional labour and emotion regulation. Discussed issues rarely appear in Polish medical magazines in spite of the increasing number of foreign publications. Key words: emotional intelligence, interpersonal relations, health personnel